2020
DOI: 10.1037/aca0000196
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the confounding effect of fluency in divergent thinking scores: Revisiting average scores to quantify artifactual correlation.

Abstract: Divergent thinking tasks are the cornerstone of creative thinking assessment. Besides fluency, the number of generated ideas, several other scores have been used to measure different aspects of idea generation in divergent thinking tasks. However, between all such scores high correlations are quite common. These correlations, in particular high correlations of any score with fluency, were interpreted as evidence for unidimensionality of divergent thinking, or as evidence for equal odds. On the other hand, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(162 citation statements)
references
References 100 publications
(205 reference statements)
4
157
1
Order By: Relevance
“…Since the measure of total creative performance has been criticized due to its high correlation with the fluency of ideas 57 59 , we also investigated, which aspects of creativity (originality, fluency) were linked with bodily movement. The regression analysis showed that both originality ( sr = 0.23, p = 0.038) and fluency ( sr = 0.25, p = 0.024) were positively and independently from each other associated with physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the measure of total creative performance has been criticized due to its high correlation with the fluency of ideas 57 59 , we also investigated, which aspects of creativity (originality, fluency) were linked with bodily movement. The regression analysis showed that both originality ( sr = 0.23, p = 0.038) and fluency ( sr = 0.25, p = 0.024) were positively and independently from each other associated with physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Since studies reported a high correlation between this additive scoring procedure of creative performance and the fluency of ideas 57,58,71 Similar to the procedure of the AU task, the originality of each picture was evaluated by three independent raters on a four-point scale ranging from 1 to 4 (ICC (2, k) = 0.79) 72 . The raters were instructed to rate the originality of the idea only, and not the drawing skills or the title of the drawing.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, usually, divergent-exploratory thinking tasks are scored for fluency, flexibility and originality (Reiter-Palmon et al, 2019) and these scores are interrelated (Forthmann et al, 2018a(Forthmann et al, , 2018bNusbaum & Silvia, 2011). In this study, our divergent thinking tasks were scored according to the EPoC Manual (Lubart et al, 2011) only with fluency (number of different ideas) and the level of flexibility of the participants has not been measured yet, nor was the originality.…”
Section: Discussionmentioning
confidence: 97%
“…There are several possible explanations for the results of the present study. First, the texters who used textisms breaking with the code would also have had a relatively low level of flexibility, which is linked to a low level of creativity (Forthmann et al, 2018a(Forthmann et al, , 2018bNusbaum & Silvia, 2011), particularly in divergent thinking (Barbot et al, 2011(Barbot et al, , 2016Barbot, Besançon, & Lubart, 2015;Wang, 2012). In contrast, it would follow TEXTISMS AND TEXTERS' CREATIVITY 20 20 that the texters who did not use textisms breaking with the code would have been more flexible, despite possessing a high level of creativity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation